Effect of Mg-Ga powder addition on the superconducting properties of MgB2 samples - Shcherbakova, O. V.; dos Santos, Dayse I. [UNESP]; Dou, S. X. (Elsevier, 2007)
MgB2 bulk samples containing different proportions of Mg-Ga powder were prepared by an in situ reaction technique. The Mg-Ga powder was obtained via high energy ball milling of a Mg-10 at.% Ga composite, which was fabricated by melting of pure magnesium and gallium metals inside encapsulated stainless steel tube at 655 °C in a controlled atmosphere. The MgB2 samples containing 0, 1, 3, 5 and 7 wt.% of MgGa addition were sintered at 650 °C for 30 min in argon atmosphere. Magnetic measurements performed at 5 K and 20 K showed improved critical current density, Jc, in the low magnetic field range for samples with MgGa addition. The critical temperature, Tc, for all samples with gallium additions is consistently higher when compared to the pure MgB2. © 2007 Elsevier B.V. All rights reserved.
Keywords: Gallium addition; MgB2 bulk; MgGa alloy; Ball milling; Powder metals; Stainless steel; Superconductivity; Critical current density; Magnesium alloys